Flexible automation and economies of scale in developing countries - Alcorta, Ludovico (1996)
The paper presents the preliminary results of an international research project undertaken in Brazil, India, Mexico, Turkey, Thailand and Venezuela on whether and to what extent flexible automation (FA) has diffused lo developing countries, and what its impact has been on product, plant and firm scale and scope. It shows that while diffusion has been rapid in the countries under study, particularly in the case of computer-numerically- controlled (CNC) machine tools, it was far slower than in developed countries. The paper analyses firm data on product scale and concludes that flexible automation does not necessarily lead to reductions in product scale and increases in product variety or scope. While there has been an increase in the 'variety' of goods produced this has often been the result of the availability of a wider range of sizes in goods and due to vertical integration into the production of components, not so much as a result of the manufacturing of different products. The paper concludes that, as compared with previous technologies, the output or capacity of most plants and firms increased, which was accompanied in some firms by lower unit costs, thus suggesting increasing optimal scale. The main reasons for increasing optimal scale are the reduction in waiting times, better factory and labour organization, higher machine efficiency and larger capital and marketing 'fixed' costs. Such findings imply that scale will continue to be a barrier to entry into industry production.